THROUGH DESIMINATION OF PROCESSED CHICKEN SHIPMENT PRODUCTS INCREASE THE EMPOWERMENT OF MOTHERS IN GUNUNG BALOHEN VILLAGE, KEBAYAK AN DISTRICT CENTRAL ACEH DISTRICT - Heriyana, Heriyana; Putri Mellita Sari, Cut; Nurainun, Nurainun (RADJA PUBLIKA, 2022)
Gunung Balohen Village is part of the Kebayakan sub-district, Central Aceh Regency. Most of the population make a living as coffee farmers. The livelihood of the wives of farmers is very dependent on the income of their husbands. In their food consumption, they often consume chicken meat than fish. They are only able to process chicken meat into a side dish for their daily food which of course the activities in processing this food are carried out by mothers. These women from Gunung Balohen Village have the potential to be able to live without depending on their husband's income and also have the potential to process food made from chicken meat so that the women are able to live independently without depending on their husband's income and increase family income. Given this kind of condition, there needs to be an effort to improve the economy and partners to improve skills with a touch of science and technology. For this reason, it is necessary to empower mothers, in an effort to increase knowledge and independence in life. The Community Partnership Program (PKM) in Gunung Balohen Village, Kebayakan District, Central Aceh Regency in collaboration with women is expected to help partner problems. The purpose of this Community Partnership Program is to empower the community by using science and technology to improve the skills and economic income of partners through processing chicken-based food, namely shredded chicken and being able to become a creative economic product. The method of carrying out the activities is carried out by (1) introducing processed food products made from nutritious modern chicken meat (2) training and mentoring in the manufacture of shredded chicken products (3) Product packaging training. The result of this activity is the increased knowledge and skills of partners in processing modern food made from chicken meat.